Health Care Education - Humphreys, John. author. aut Link
XI, 180 p. 1 illus.
Keywords: Sometime in the 1980s, Norbert Singer, the then Director of Thames Polytechnic, became interested in the idea of becoming involved in nurse educa tion. Project 2000 had been published. In those days, there were three qualified nurses in the Polytechnic: all in the School of Post Compulsory Education and Training, and all involved in the training of nurse tutors. Knowing this, he tele phoned the Head of School: 'Take an interest in this', he said, 'Let's see how far it can go'. Singer had perceived the possibility of a new market - a major oppor tunity for his institution. Whereas we had been active in various minor collabor ations before, after that telephone call the development of health care education became a strategic priority. Now Thames Polytechnic is the University of Greenwich. We have a Faculty of Health with P2000 and 100+ staff; a major interest in physiotherapy training through a national agreement with the Chartered Society of Physiotherapy; the UK's first operational ENB Higher Award with Princess Alexandra and Newham College of Nursing and Midwifery and 1000+ students working for Greenwich awards through Nursing Times Open Learning. These developments are indicative of the scale and scope of recent changes in health care education.